The Didactic Domino in the English teaching as a foreign language and its technical application - Marisel Rivas Reyes; Raiza Texidor Pellón; Rosa María González Ramos (Universidad de Ciencias Médicas de La Habana, 2015)
Introduction: the didactic game Domino in the teaching of English as a foreign language with general and specific language goals in the Medical University is far from showing lack of maturity and professionalism. It is a teaching mean that can be used at any moment of the lesson making it nice and efficient. Objective: to describe the use of the didactic game Domino as a teaching mean in the English subject with general and specific language goals and to evaluate the results of its application. Material and Methods: a cross-sectional descriptive study was conducted with theoretical methods of analysis and synthesis of bibliographical and documentary reviews on the theme, which allows us to gather information. Results: it could be noticed that the use of the didactic game Domino is very well received by the students for the development of linguistics and communicative skills. It gives the students opportunity to participate in their knowledge management. Working in pairs or groups, it strengthens and promotes values such as solidarity and comradeship in a motivated, interesting and pleasant way. Conclusions: the use of the didactic game Domino as a teaching mean was described and the results of its application were evaluated. Keywords: didactic game, general English language, technical English language, teaching mean.